Handbook of Community Sentiment - Miller, Monica K.; Miller, Monica K.; Blumenthal, Jeremy A.; Blumenthal, Jeremy A.; Chamberlain, Jared.; Chamberlain, Jared. (Springer New York : Imprint: Springer, 2015)
This in-depth investigation of community sentiment examines why and how community sentiment is studied, how it may change or be changed, and its reciprocal relationship with laws and policy. Laws affecting children and the family, for instance actual and proposed laws regarding marriage and divorce, campus safety, sex offender registration are used to  discuss the study of community sentiment. Yet, the book is broad enough to inform readers about sentiment toward issues beyond the law. The book also considers the relationships between community sentiment and individual attitudes, media, perceptions about justice, and negative legal, personal, and societal outcomes. This range of carefully chosen chapters condenses a broad knowledge base into a manageable and highly useful  “go to” book about the study of community sentiment toward any topic. Among the topics covered: The reciprocal relationship between media, community sentiment and policy. Various measures and methodology used in gauging community sentiment toward law and other topics. Factors that influence or change sentiment. Relationships between attitude theory and community sentiment. Links between community sentiment and perceptions of justice. Unintended consequences of policy responses. Can community sentiment lead to ineffective laws? The Handbook of Community Sentiment is an expansive resource of interest to a variety of practitioners and researchers—psychologists, sociologists, criminal justice professionals and criminologists, and political scientists--as well as students in these and related fields.